The painted hills - Kress, Harold F., 1913-1999; primer actor mencionado en 511; Hull, Alexander; Loew's Incorporated; Cinetel Films ([Los Angeles, CA] : Loew's Incorporated, 1951)
After years of prospecting, Jonathan finally strikes gold. He returns to town only to discover that his partner has since died and left Tommy fatherless. He decides to leave Shep (played by Lassie) with Tommy to cheer him up. Meanwhile, Jonathan's new partner, Lin, isn't interested in sharing the gold, and lures Jonathan to his death. --
Based on the novel: Shep of the painted hills / Alexander Hull.
Lassie, Paul Kelly, Bruce Cowling, Gary Gray, Art Smith.
Cinematographers, Alfred Gilks, Harold Lipstein; editor, Newell B. Willis; music, Daniele Amfitheatrof.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Lassie (Dog) -- Drama; Gold mines and mining -- Drama; Dogs -- Drama; Lassie (Fictitious character); Action and adventure films; Feature films; Internet videos; Streaming video